The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10750-007-9200-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability of bio-optical parameters in two North-European large lakes

Abstract: The bio-optical properties of some NorthEuropean large lakes were examined during 1995-2005 using field data and laboratory measurements. The key variables were optically active substances (OAS: chlorophyll, total suspended matter and dissolved organic matter), Secchi depth, and the ''spectrometric'' and diffuse light attenuation coefficients. Our main study sites were Lake Peipsi and Lake Võrtsjärv in Estonia, both eutrophic with mean Secchi depth below 3 m. The measured water parameters were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…Using the OWT classification performed in this study, it is possible to follow the movements of river water masses. Additionally, the OWT classification for larger lakes showed a reasonable correspondence with the results of previous studies [42][43][44][45]. Some small lakes and pixels affected by the adjacency effect were often classified as Clear.…”
Section: Discussionsupporting
confidence: 86%
“…Using the OWT classification performed in this study, it is possible to follow the movements of river water masses. Additionally, the OWT classification for larger lakes showed a reasonable correspondence with the results of previous studies [42][43][44][45]. Some small lakes and pixels affected by the adjacency effect were often classified as Clear.…”
Section: Discussionsupporting
confidence: 86%
“…Our Lake Taihu short‐time series analyses of wind speed, TSM concentration, and bio‐optical properties revealed that wind‐driven sediment resuspension was indeed the primary force controlling the short‐term variability in the underwater light attenuation. This is in agreement with other studies in shallow lakes and bays, using short‐term, high‐frequency observations, long‐term monitoring, remote sensing, and numerical simulations, which show that wind‐driven sediment resuspension can significantly change the concentrations of OASs and water bio‐optical properties [ Paavel et al ., ; Chen et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The driving factors in large, shallow lakes, particularly the wind‐driven sediment resuspension, rivers input, and ship waves disturbance, lead to a wide range of temporal and spatial scales of suspended matter, phytoplankton, and SAV [ Qin et al ., , ; Istvánovics et al ., ]. Of all the dynamic disturbance effects, wind‐induced sediment resuspension is the one that most directly reduces water transparency and euphotic depth, thereby affecting the primary productivity in the lake, as well as the seasonal and spatial distribution of the SAV [ Schallenberg and Burns , ; Paavel et al ., ; Carr et al ., ; Verspecht and Pattiaratchi , ].…”
Section: Introductionmentioning
confidence: 99%
“…Its water is optically turbid and the underwater light climate is very strongly affected by the lake's water level and ice conditions [30]. Transparency measured with the Secchi disk is in the range of 0.3-1.6 m and chl-a varies from 20 to 102 mg m -3 [31]. Its catchment area (3100 km 2 ) makes up about 7% of Estonian territory and, thus, contributes significantly to the Estonian natural CO 2 budget.…”
Section: Lake Võrtsjärvmentioning
confidence: 99%